Student’s knowledge and awareness of 3R in relation to the implementation of the P5 “Sustainable Lifestyle” theme - Agung Mulyono; Asriah Nurdini Mardiyyaningsih; Wolly Candramila (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2026)
The Strengthening Pancasila Student Profile (P5) project program is a policy within the Merdeka Curriculum aimed at developing 21st-century character and competencies through project-based learning. This study aims to evaluate the effectiveness of the implementation of the P5 project with the Sustainable Lifestyle theme on 3R-related knowledge and awareness among ninth-grade students at SMP Negeri 2 Sungai Raya. The method used was nex post facto correlational design with a quantitative descriptive approach and simple linear regression analysis. The research instruments included a knowledge test and a 3R awareness questionnaire. The results showed that the average scores for P5 implementation (74.73), knowledge (79.11), and awareness (76.74) were all categorized as 'good.' The simple regression analysis indicated that students' knowledge (β = 0.448; p = 0.001; R = 0.166) and students' awareness (β = 0.097; p = 0.003; R = 0.04) were positively influenced, with knowledge showing a more dominant effect than awareness. These findings suggest linear relationship between the implementation of the Sustainable Lifestyle-themed P5 project and the strengthening of cognitive (knowledge) and affective (awareness) aspects related to environmental issues.Abstrak. Program Proyek Penguatan Profil Pelajar Pancasila (P5) merupakan kebijakan dalam Kurikulum Merdeka yang bertujuan membentuk karakter dan kompetensi abad ke-21 melalui pembelajaran berbasis proyek. Penelitian ini bertujuan mengevaluasi keberhasilan implementasi P5 tema Gaya Hidup Berkelanjutan terhadap pengetahuan dan kesadaran 3R pada siswa kelas IX di SMP Negeri 2 Sungai Raya. Desain penelitian adalah korelasi ex post-facto dengan pendekatan deskriptif kuantitatif dan uji regresi linear sederhana. Instrumen penelitian berupa tes pengetahuan dan angket kesadaran 3R. Hasil penelitian menunjukkan nilai rata-rata implementasi P5 sebesar 74,73; pengetahuan 79,11; dan kesadaran 76,74, seluruhnya dikategorikan ‘baik’. Uji regresi sederhana menunjukkan bahwa pengetahuan siswa (β = 0,448; p = 0,001; R = 0,166) dan kesadaran siswa (β = 0,097; p = 0,003; R = 0,04) dengan pengaruh pengetahuan lebih dominan daripada kesadaran. Temuan ini menunjukkan ada linearitas hubungan antara implementasi P5 tema Gaya Hidup Berkelanjutan dengan penguatan aspek kognitif (pengetahuan) dan afektif (kesadaran) mengenai permasalahan lingkungan.